México-Cuba : two projects and a structural distancing under the neoliberal model (Colección, 2017)
The estrangement in Mexico-Cuba relationship had its origin in the structural difference of the respective economic and political projects that the governments of these countries defined and implemented since the eighties of the last century until the end of 2015. The structural estrangement in bilateral relations began since the 1990s, due to the implementation of the neoliberal model in Mexico as well as the compartmentalization of Mexican foreign policy. Historically, Mexico-Cuba relationship has been conditioned by the role of US foreign policy and its ability to influence the decisions of these two nations
Keywords: Foreign policy; Mexico; Cuba; Compartmentalization; Economic blockade; Neo-liberalism